The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-42121/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA Barcoding Reveals Cryptic Diversity in the Underestimated Genus Triplophysa (Cypriniformes: Cobitidae, Nemacheilinae) from the Northeastern Qinghai-Tibet Plateau

Abstract: Background: The northeastern part of the Qinghai-Tibet Plateau (QTP) presents a high number of plateau loach species. As one of the three major groups of fishes distributed on the QTP, plateau loach has high ecological value. However, the taxonomy and systematics of these fish are still controversial, and a large number of new species have been reported. The reason for this phenomenon is that the degree of morphological variation is low, the phylogenetic information provided by morphological and anatomical fea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…While single‐locus data has its limitations in making inferences about historical demography (Matumba et al, 2020), DNA barcoding, or the use of other single‐locus DNA markers, has provided tremendous insight into identifying evolutionary significant units and providing information on species in further need of exploration (Bousjein et al, 2021; León‐Tapia, 2021; Nneji et al, 2020; Sholihah et al, 2020; Wang et al, 2020). These data are particularly helpful when aiming to explore broad‐scale patterns such as those on a continental scale (Dincă et al, 2021) or across species (Doorenweerd et al, 2020), especially for a large number of taxonomic groups, as demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…While single‐locus data has its limitations in making inferences about historical demography (Matumba et al, 2020), DNA barcoding, or the use of other single‐locus DNA markers, has provided tremendous insight into identifying evolutionary significant units and providing information on species in further need of exploration (Bousjein et al, 2021; León‐Tapia, 2021; Nneji et al, 2020; Sholihah et al, 2020; Wang et al, 2020). These data are particularly helpful when aiming to explore broad‐scale patterns such as those on a continental scale (Dincă et al, 2021) or across species (Doorenweerd et al, 2020), especially for a large number of taxonomic groups, as demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…While single-locus data has its limitations in making inferences about historical demography (Matumba et al 2020), DNA barcoding, or the use of other single-locus DNA markers has provided tremendous insight into identifying evolutionary significant units and providing information on species in further need of exploration (Sholihah et al 2020;Wang et al 2020;Nneji et al 2020;Bousjein et al 2021;León-Tapia 2021). These data are particularly helpful when aiming to explore broad-scale patterns such as those on a continental scale (Dinça et al 2021) or across species (Doorenweerd et al 2020), especially for a large number of taxonomic groups, as demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…Te molecular approach is considered backbone for evaluating fsh species evolutionary variation and conservation process for biological resources [27]. Unfortunately, as far as Nucleotide composition and genetic pairwise distance recommend that the calculated species of subfamily Nemacheilinae are organically dissimilar [6]. Te fsh diversity study was conducted to evaluate the genetic diversity and cryptic species identifcation of the genus Triplophysa in the fresh waters of Malakand Division through a molecular and morphological approaches [28].…”
Section: Disscussionmentioning
confidence: 99%
“…Triplophysa has a long confusing classifcation history therefore, the cryptic diversity of the genus Triplophysa will be examined in the study. It belongs to the subfamily Nemacheilinae [6]. Te diversity of fsh is so difcult on morphologically based therefore mitochondrial and nuclear gene sequences have been routinely used because the mitochondrial genomic part is mostly carrying heredity information [7] Te current investigation provides information on the genotype of a few Nemachilidae species from Iranian inland waters, including Paraschistura bampurensis, Oxynoemacheilus kiabii, Turcinemacheilus saadii, Leuciscine cyprinid, Alburnoides bipunctatus and Alburnus alburnus use mitochondrial gene COI [8].…”
Section: Introductionmentioning
confidence: 99%